Homeopathic prescribing for chronic conditions in feline and canine veterinary practice - Mathie, Robert T.; Baitson, Elizabeth S.; Hansen, Lise; Elliott, Mark F.; Hoare, John (Homeopathy, 2010)
Introduction: The peer-review literature contains no controlled clinical research of homeopathy in cats and very little in dogs.Main objective: To collect clinical outcomes data systematically from individualised homeopathic treatment of cats and dogs that would help to inform controlled research in feline and canine homeopathy.Methods: Twenty-one homeopathic veterinary surgeons recorded data systematically from consecutive feline and canine patients over a 12-month period. Records included: date; patient and owner identity (anonymised); medical problem treated; whether new or follow-up (FU) appointment; chronic or acute condition; owner-assessed clinical outcome (7-point scale, range −3 to +3) compared with first appointment.Results: Data from 400 cats comprised a total of 372 individual chronic problems, of which 270 had FU assessment. Data from 1504 dogs comprised a total of 1408 individual chronic problems, of which 1070 had FU assessment. In both species, 22% of FUs in chronic cases received conventional medicines concurrently. In cats, 117 different chronic medical conditions in total were treated with homeopathy. Five of those conditions included ≥20 cases, in which owner-reported outcomes (in decreasing rank order of frequency) were: dermatitis (69.6% patients with +2 or +3 outcome, 0% patients with −2 or −3 outcome); renal failure (57.1%, 14.3%); overgrooming (57.1%, 7.2%); arthritis (80.0%, 0%); hyperthyroidism (66.7%, 0%). In dogs, of 301 different chronic medical conditions treated in total, those most commonly recorded (≥20 cases) were: dermatitis (66.2% with +2 or +3 outcome, 5.4% with −2 or −3 outcome); arthritis (80.2%, 0.8%); pyoderma (75.8%, 0%); colitis (85.2%, 0%); fear (31.6%, 0%); epilepsy (63.6%, 4.5%); otitis externa (72.7%, 0%); diarrhoea (68.2%, 0%); urinary incontinence (73.7%, 0%); aggression (57.1%, 0%); spondylosis (81.0%, 0%); lymphoma (40.0%, 6.7%).Conclusions: A programme of controlled research in veterinary homeopathy for these feline and canine conditions is clearly indicated.
Keywords: Homeopathy; Clinical outcomes; Arthritis; Dermatitis; Cats; Dogs